Innate immunity in C. elegans - Ewbank, Jonathan (Henry Stewart Talks, 2009)
Anatomy of C. elegans, C. elegans as an experimental animal, Pheromone signalling and pathogen detection, Specific and general transcriptional responses to bacterial infection, Necrosis, Fungal infection and injury induce antimicrobial peptide genes, Signal transduction pathways that control antimicrobial peptide gene expression
Updated at 2011/11/03, Archived at 2018/02/28